SISTEM INFORMASI PELAYANAN PELANGGAN BERBASIS WEBSITE PADA PERUSAHAAN DAERAH AIR MINUM WAY RILAU BANDAR LAMPUNG - Wahyuni, Tri (Jurnal Informatika, 2008)
[In] globalization era [of] where information and technological [of] walking. Swiftly both representing key to step more go forward and the time became very worth where all activity which execute structure have to and earn to give amenity obtained in executing activity. For example [is] the forwarding of information and denunciating in online internet, so that socialize and the client;Â  subscriber [do] not have to visit upon place or the company.Referning to above matter to make functioned situs web interactive alternatively from process of [is] forwarding of client; subscriber denunciating to company of district of drinking water of Way Rilau Bandar Lampung.This situs web designed, consisted of some page; yard, where this page; yard there [is] using Flash as especial menu appearance with [his/its] extensions file .swf and partial; some again represent solidarity [of] [ among/between] HTML, script ASP with extensions .asp. This situs use Access as data bases.Result form this implementation web [is] situs web of client; subscriber service, this situs web have two facility that is user or wearer and also for operator. Keyword : Website, Flash, HTML, Script ASP, Access as data bases.